1437 Markers of the Metabolic Syndrome and Physical Activity in Teenage Children Born Preterm. (October 2012) - Tinnion, R; Hollingsworth, K; Basterfield, L; Trenell, M; Cheetham, T; Embleton, N
Abstract : Background and Aims: The worldwide increase in the Metabolic Syndrome is associated with adverse health outcomes and significant healthcare costs. Early life exposures are key factors in determining later health. Children born preterm appear to be at higher risks of developing insulin resistance. We aimed to determine the prevalence of novel metabolic biomarkers in a cohort of teenage children who were born preterm (< =34 weeks gestation) and correlate these with physical activity. Methods: We studied 24 children using standard techniques including auxology, body composition (BODPOD™), insulin resistance (fasting and post-glucose load) and daily activity (Actigraph™ and Actilife™ software). We measured 31-P and 1-H magnetic resonance spectroscopy (MRS) and assessed intra-hepatic lipid (IHL) content and phospho-creatine recovery after standardised exercise within the MR scanner. Results: IHL was associated with increases in body mass and fat mass index (% body fat/height 2 ). There was a weak association between glucose levels and muscle recovery time with increased IHL. Recovery from exercise was correlated with % time spent in daily moderate-to-vigorous physical activity (MVPA) and sedentary activity. Only 5 children achieved an activity time within 10% of the recommended 60 minutes or more of MVPA per day (mean:39 minutes). Conclusions: Children born preterm have evidence of adverse metabolic outcomes in later life. IHL deposition is related to overall fatness, and may be significant in adverse metabolic processes. Measured physical activity correlates with the ability of muscle to recover from a defined exercise. Improving MVPA may result in health benefits.